Effectiveness of Corridor VI UNNES-UNDIP Route As A Means of Student Mobility - Salsabila, Thouf; Kustamara, Segi Megawati; Wijayanti, Dina; Situmorang, Ninda Arini Rotua (Universitas Negeri Semarang, 2024)
Semarang, a growing metropolitan city, is experiencing significant mobility challenges. This article focuses on evaluating the effectiveness of public transportation Corridor VI Route UNNES-UNDIP in meeting the mobility needs of students. The research method used is descriptive qualitative to be able to measure the effectiveness of services from the user's perspective. The results showed that public transportation services on Corridor VI UNNES-UNDIP Route have a good level of effectiveness in terms of mobilization, safety, comfort, timeliness, information, and payment access. However, there are still areas that need to be improved, such as the use of technology to improve service quality, infrastructure improvements, and more effective promotion to the public. With these improvements in effectiveness, public transportation can help improve student mobility, encourage the use of sustainable transportation, and reduce congestion and pollution in Semarang City.